(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical characteristics, paraclinical findings, and treatment outcomes of patients with diabetic foot infection treated at Department of Internal Medicine No. 3, Viet Tiep Friendship Hospital, Hai Phong, Vietnam, during 2023–2024. Subjects and Methods: A total of 65 inpatients with diabetic foot infection were included. This was a descriptive cross-sectional study using convenience sampling. Results: The mean age was 66.1 ± 11.5 years. The proportion of smokers was 29.2%, and 64.6% had hypertension. Clinically, most patients had Wagner grade 2–3 lesions (92.3%). The duration of ulcer prior to admission was <7 days in the majority of cases (87.7%).Regarding paraclinical findings, the mean HbA1c was 9.1 ± 2.4, with 81.5% having HbA1c ≥7%. The mean ankle–brachial index (ABI) was 0.95 ± 0.19, and the prevalence of peripheral arterial disease (PAD) was 18.5%.Favorable and moderate treatment outcomes accounted for 89.2%, while the amputation rate was 6.2%. Most patients were treated with a single antibiotic and local wound care.An ulcer duration ≥7 days was associated with a higher likelihood of poor outcomes or amputation (OR = 18.0, p = 0.002), and arterial stenosis was also associated with poor outcomes (OR = 5.11, p < 0.05), suggesting the importance of early detection and assessment of limb perfusion. Conclusions: Short-term in-hospital treatment outcomes were generally favorable, with a predominance of healing and improvement and a low amputation rate. Ulcer duration ≥7 days and lower limb arterial stenosis were significantly associated with an increased likelihood of poor treatment outcomes. These findings suggest the importance of early lesion detection, glycemic control, and assessment of lower limb perfusion in supporting improved in-hospital treatment response.